APPLICATION OF INTUITIONISTIC FUZZY SETS IN RESEARCH QUESTIONNAIRE - Ejegwa, P. A. (Journal of Global Research in Mathematical Archives(JGRMA), 2015)
An application of intuitionistic fuzzy sets in research questionnaire construction, filling, analysis, and interpretation is given. Respondents’ decision is obtained assuming questionnaire is distributed among respondents. The respondents’ decision is converted into intuitionistic fuzzy values, analysed, and from which interpretation is drawn. Keywords:fuzzy sets, intuitionistic fuzzy sets, questionnaire, respondents, sociometry.